The Ecological Vulnerability Analysis of Three River Ecosystems of Santiago de Cuba - Morell Bayard, Alina de la Caridad (2026)
River ecosystems are currently more sensitive to natural or anthropogenic disturbances, which influence the quality of their goods and services. To protect their sustainable use and services, early detection of potentially harmful changes in their functional capacities is necessary. Vulnerability analysis provides information on their weaknesses and resilience after an impact. The objective of this research was to assess the ecological vulnerability of three river ecosystems in the municipality of Santiago de Cuba: San Juan, Las Guásimas, and Carpintero. A system of 32 indicators, previously selected after a systematic review of 210 articles published between 2019 and 2024, was used for this purpose. Twenty-two indicators were selected through expert consultation, distributed among four general, four specific, and fourteen basic indicators. Synthesis matrices were developed for the analysis, the results of which demonstrated that the San Juan and Las Guásimas ecosystems exhibit high ecological vulnerability, while Carpintero is classified as having medium vulnerability. These results are primarily associated with poor surface water quality, high ecosystem fragmentation, and an increase in prolonged periods of drought.